Simplify: (Algebra)
a. 2j-3o-5e+l-j+4o+6e
b. -7d+a+2v-i+8d-v+2i+d2
c. 4a+12r-i+a2-11r-3a+n+a3
d. r3-11a+12a-sh+2sh+i+d
e. t5+a-2a+2r-r+l-2l+a4+3n-2n
f. -11i2-r+2r+a3-4d+3d-a
g. -9r+10r+a-s3-2a+2s3+u-l
h. -4d+2a3-a3+5n+iz-4n
i. 16a5-2(l-y+y3)-a+d2-d3+in
j. -5z-e+2e-y5-n+2n-a5-l+l3-i3
k. m-3m-a+2a-m3-2m5-a3-d+l+i4
l. -4t3+5t3+3o-2o+2m-m-r3-is+2is
m. -5j+h-2h+4j-3a+6a-d3
n. r3-3u+2u-st+a3-2a3-5m+4m
o. -6b5-a+4h-3h+18a2+3a-d4+i2-2i2-4r4
p. 13s5-2o+5n3-12s5-6n3+3o+a5
q. -17m+16m-3u+r3+2u-2r3+a4+d4

Respuesta :

Answer:

[tex]2j-3o-5e+l-j+4o+6e= e+j+l+o[/tex]

[tex]-7d+a+2v-i+8d-v+2i+d^2 = d^2+a+d+i+v[/tex]

[tex]4a+12r-i+a^2-11r-3a+n+a^3 = a^3+a^2+a-i+n+r[/tex]

[tex]r^3-11a+12a-sh+2sh+i+d= r^3+a+sh+i+d[/tex]

[tex]t^5+a-2a+2r-r+l-2l+a^4+3n-2n = t^5-a+r-l+a^4+n[/tex]

[tex]-11i^2-r+2r+a^3-4d+3d-a = -11i^2+r+a^3-d-a[/tex]

[tex]-9r+10r+a-s^3-2a+2s^3+u-l = r-a+s^3+u-l[/tex]

[tex]-4d+2a^3-a^3+5n+iz-4n = -4d+a^3+n+iz[/tex]

[tex]16a^5-2(l-y+y3)-a+d^2-d^3+in = 16a^5-2l-2y+2y3-a+d^2-d^3+in[/tex]

[tex]-5z-e+2e-y^5-n+2n-a^5-l+l^3-i^3 = -5z+e-y^5+n-a^5-l+l^3-i^3[/tex]

[tex]-2m+a-m^3-2m^5-a^3-d+l+i^4= -2m+a-m^3-2m^5-a^3-d+l+i^4[/tex]

[tex]-4t^3+5t^3+3o-2o+2m-m-r^3-is+2is = t^3+o+m-r^3+is[/tex]

[tex]-5j+h-2h+4j-3a+6a-d^3 = -5j-h+4j+3a-d^3[/tex]

[tex]r^3-3u+2u-st+a^3-2a^3-5m+4m = r^3-u-st-a^3-m[/tex]

[tex]-6b^5-a+4h-3h+18a^2+3a-d^4+i^2-2i^2-4r^4= -6b^5+3a-a+4h-3h+18a^2-d^4+i^2-2i^2-4r^4[/tex]

[tex]13s^5-2o+5n^3-12s^5-6n^3+3o+a^5=s^5+o-n^3+a^5[/tex]

[tex]-17m+16m-3u+r^3+2u-2r^3+a^4+d^4= -1m+-u-r^3+a^4+d^4[/tex]

Step-by-step explanation:

[tex]a.\ 2j-3o-5e+l-j+4o+6e[/tex]

Collect Like Terms

[tex]-5e+6e+2j-j+l+4o-3o[/tex]

[tex]e+j+l+o[/tex]

Hence:

[tex]2j-3o-5e+l-j+4o+6e= e+j+l+o[/tex]

[tex]b.\ -7d+a+2v-i+8d-v+2i+d^2[/tex]

Collect Like Terms

[tex]d^2+a+8d-7d-i+2i+2v-v[/tex]

[tex]d^2+a+d+i+v[/tex]

Hence:

[tex]-7d+a+2v-i+8d-v+2i+d^2 = d^2+a+d+i+v[/tex]

[tex]c.\ 4a+12r-i+a^2-11r-3a+n+a^3[/tex]

Collect Like Terms

[tex]a^3+a^2+4a-3a-i+n+12r-11r[/tex]

[tex]a^3+a^2+a-i+n+r[/tex]

Hence:

[tex]4a+12r-i+a^2-11r-3a+n+a^3 = a^3+a^2+a-i+n+r[/tex]

[tex]d.\ r^3-11a+12a-sh+2sh+i+d[/tex]

Evaluate like terms

[tex]r^3+a+sh+i+d[/tex]

Hence:

[tex]r^3-11a+12a-sh+2sh+i+d= r^3+a+sh+i+d[/tex]

[tex]e.\ t^5+a-2a+2r-r+l-2l+a^4+3n-2n[/tex]

Evaluate like terms

[tex]t^5-a+r-l+a^4+n[/tex]

Hence:

[tex]t^5+a-2a+2r-r+l-2l+a^4+3n-2n = t^5-a+r-l+a^4+n[/tex]

[tex]f.\ -11i^2-r+2r+a^3-4d+3d-a[/tex]

Evaluate Like Terms

[tex]-11i^2+r+a^3-d-a[/tex]

Hence:

[tex]-11i^2-r+2r+a^3-4d+3d-a = -11i^2+r+a^3-d-a[/tex]

[tex]g.\ -9r+10r+a-s^3-2a+2s^3+u-l[/tex]

Collect Like Terms

[tex]-9r+10r+a-2a+2s^3-s^3+u-l[/tex]

[tex]r-a+s^3+u-l[/tex]

Hence:

[tex]-9r+10r+a-s^3-2a+2s^3+u-l = r-a+s^3+u-l[/tex]

[tex]h.\ -4d+2a^3-a^3+5n+iz-4n[/tex]

Collect Like Terms

[tex]-4d+2a^3-a^3+5n-4n+iz[/tex]

[tex]-4d+a^3+n+iz[/tex]

Hence:

[tex]-4d+2a^3-a^3+5n+iz-4n = -4d+a^3+n+iz[/tex]

[tex]i.\ 16a^5-2(l-y+y3)-a+d^2-d^3+in[/tex]

Open bracket

[tex]16a^5-2l-2y+2y3-a+d^2-d^3+in[/tex]

Hence:

[tex]16a^5-2(l-y+y3)-a+d^2-d^3+in = 16a^5-2l-2y+2y3-a+d^2-d^3+in[/tex]

[tex]j.\ -5z-e+2e-y^5-n+2n-a^5-l+l^3-i^3[/tex]

Evaluate like terms

[tex]-5z+e-y^5+n-a^5-l+l^3-i^3[/tex]

Hence:

[tex]-5z-e+2e-y^5-n+2n-a^5-l+l^3-i^3 = -5z+e-y^5+n-a^5-l+l^3-i^3[/tex]

[tex]k.\ m-3m-a+2a-m^3-2m^5-a^3-d+l+i^4[/tex]

Evaluate like terms

[tex]-2m+a-m^3-2m^5-a^3-d+l+i^4[/tex]

Hence:

[tex]-2m+a-m^3-2m^5-a^3-d+l+i^4= -2m+a-m^3-2m^5-a^3-d+l+i^4[/tex]

[tex]l.\ -4t^3+5t^3+3o-2o+2m-m-r^3-is+2is[/tex]

Evaluate like terms

[tex]t^3+o+m-r^3+is[/tex]

Hence

[tex]-4t^3+5t^3+3o-2o+2m-m-r^3-is+2is = t^3+o+m-r^3+is[/tex]

[tex]m.\ -5j+h-2h+4j-3a+6a-d^3[/tex]

Evaluate like terms

[tex]-5j-h+4j+3a-d^3[/tex]

Hence:

[tex]-5j+h-2h+4j-3a+6a-d^3 = -5j-h+4j+3a-d^3[/tex]

[tex]n.\ r^3-3u+2u-st+a^3-2a^3-5m+4m[/tex]

Evaluate like terms

[tex]r^3-u-st-a^3-m[/tex]

Hence:

[tex]r^3-3u+2u-st+a^3-2a^3-5m+4m = r^3-u-st-a^3-m[/tex]

[tex]o.\ -6b^5-a+4h-3h+18a^2+3a-d^4+i^2-2i^2-4r^4[/tex]

Collect Like Terms

[tex]-6b^5+3a-a+4h-3h+18a^2-d^4+i^2-2i^2-4r^4[/tex]

[tex]-6b^5+2a+h+18a^2-d^4-i^2-4r^4[/tex]

Hence:

[tex]-6b^5-a+4h-3h+18a^2+3a-d^4+i^2-2i^2-4r^4= -6b^5+3a-a+4h-3h+18a^2-d^4+i^2-2i^2-4r^4[/tex]

[tex]p.\ 13s^5-2o+5n^3-12s^5-6n^3+3o+a^5[/tex]

Collect Like Terms

[tex]13s^5-12s^5-2o+3o+5n^3-6n^3+a^5[/tex]

[tex]s^5+o-n^3+a^5[/tex]

Hence:

[tex]13s^5-2o+5n^3-12s^5-6n^3+3o+a^5=s^5+o-n^3+a^5[/tex]

[tex]q.\ -17m+16m-3u+r^3+2u-2r^3+a^4+d^4[/tex]

Collect Like Terms

[tex]-17m+16m+2u-3u+r^3-2r^3+a^4+d^4[/tex]

[tex]-m+-u-r^3+a^4+d^4[/tex]

Hence:

[tex]-17m+16m-3u+r^3+2u-2r^3+a^4+d^4= -1m+-u-r^3+a^4+d^4[/tex]